A sequence model for air traffic flow management rerouting problem - Diao, Xudong (2020)
With the continuous growth of air transportation industry, the current Air Traffic Management systems can hardly meet the demand recently. In this work, an integer optimization model for Air Traffic Flow Management (ATFM) which integrates 4D trajectory-based operations is proposed to improve the situation. Besides addressing the issues of rerouting, ground-holding delay, fuel consumption and flight cancellation on a flight-by-flight basis, the model also employs sector-less airspace configurations. In order to solve the model efficiently, Dantzig-Wolfe decomposition and a heuristic approach via column generation are developed to generate 4D conflict-free trajectories for each flight. By applying commercial optimization software, solutions could be obtained in 20 min for the ATFM rerouting problems of the whole Southeast Asia region.